Understanding the knowledge transfer process in the flood management domain - Yahya H.; Rodzi M.Z.M.; Ahmad M.N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Numerous studies have shown that disasters can be managed effectively using a knowledge management system (KMS). To develop an effective KMS, several components need to be studied. One of the important components in KMS is knowledge transfer. This study attempts to identify the essential sub-processes of knowledge transfer in the context of flood management in Malaysia. We propose a conceptual knowledge transfer model based on these processes. © 2014 IEEE.